2008
DOI: 10.1021/bi801268f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Quinolinate Synthases from Escherichia coli, Mycobacterium tuberculosis, and Pyrococcus horikoshii Indicates That [4Fe-4S] Clusters Are Common Cofactors throughout This Class of Enzymes

Abstract: Quinolinate synthase (NadA) catalyzes a unique condensation reaction between iminoaspartate and dihydroxyacetone phosphate, affording quinolinic acid, a central intermediate in the biosynthesis of nicotinamide adenine dinucleotide (NAD). Iminoaspartate is generated via the action of L-aspartate oxidase (NadB), which catalyzes the first step in the biosynthesis of NAD in most prokaryotes. NadA from Escherichia coli was hypothesized to contain an iron-sulfur cluster as early as 1991, because of its observed labi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…For example, bacteria can neo-synthesize quinolinic acid (Marinoni et al, 2008; Reichmann et al, 2015; Sakuraba et al, 2005; Saunders et al, 2008), and unique prokaryotic enzymes can degrade kynurenic acid (Taniuchi and Hayaishi, 1963). Bacterial neosynthesis of quinolinic acid begins with the condensation of iminoaspartate with dihydroxyacetone, and the latter compound also inhibits α-amino-β-carboxymuconate-ε-semialdehyde decarboxylase (ACMSD) (Garavaglia et al, 2009).…”
Section: The Gut-brain Axismentioning
confidence: 99%
“…For example, bacteria can neo-synthesize quinolinic acid (Marinoni et al, 2008; Reichmann et al, 2015; Sakuraba et al, 2005; Saunders et al, 2008), and unique prokaryotic enzymes can degrade kynurenic acid (Taniuchi and Hayaishi, 1963). Bacterial neosynthesis of quinolinic acid begins with the condensation of iminoaspartate with dihydroxyacetone, and the latter compound also inhibits α-amino-β-carboxymuconate-ε-semialdehyde decarboxylase (ACMSD) (Garavaglia et al, 2009).…”
Section: The Gut-brain Axismentioning
confidence: 99%
“…both catalyze a dehydration process and coordinate a Fe 4 S 4 cluster with only three cysteine protein ligands, which in NadA are organized in a CX86 -112CX 86-99C motif. [5][6][7] Consequently, it was suggested that the unique iron site of the NadA Fe 4 S 4 cluster should also be directly involved in dehydration steps, acting as a Lewis acid. Partial mechanistic information has been obtained from the two available crystal structures of NadA, 8 , 9 which correspond to the inactive apo form of the enzyme.…”
mentioning
confidence: 99%
“…monodentate or bidentate coordination of the substrate) (47). The interacting iron atom could facilitate nucleophilic attack at the sulfate sulfur by acting as a Lewis acid, analogous to aconitase (29).…”
Section: Discussionmentioning
confidence: 99%